Complete chloroplast genome sequences of Pyropia dentata (Bangiales, Rhodophyta) - Sung-Je Choi; Yonguk Kim; Jawon Shin; Dong-Wook Kim; Hak-Sung Lee; Chulyung Choi (Mitochondrial DNA. Part B. Resources, 2020)
Pyropia dentata is an economically valuable species in seaweed aquaculture in the southwest coastal regions of Korea. Herein, we determined the complete chloroplast (cp) genome sequence of P. dentata using PacBio resequencing data. The whole cp genome is 192,266 bp in size, encodes 148 genes (including 92 protein-coding, 44 tRNA-coding, and 12 rRNA-coding genes), and lacks inverted repeat (IR) regions. A maximum likelihood phylogenetic analysis demonstrated that P. dentata was most closely related to P. haitanensis. The cp genome will provide a useful reference for further studies of P. dentata.